Evaluasi Kinerja Guru SMA Bersertifikasi Dengan Model Charlotte Danielson Di SMA Negeri - Erfy Melany Lalupanda; Bambang Suteng Sulasmono; Ade Iriani (Universitas Kristen Satya Wacana, 2019)
The research aims to evaluate the performance of certified teachers at SMA Negeri 1 Waingapu, East Sumba Regency. The type of this research is evaluative research. The subject of this research is 7 teachers certified in SMA Negeri 1 Waingapu. The teacher performance evaluation model used is the Charlotte Danielson model that evaluates teacher performance in 4 domains: (1) Planning and Preparation, (2) Classroom Environment, (3) Instruction, and (4) Professional Responsibility. Data collection techniques that used are document studies, observation, and interviews. The data validity test is done by triangulation technique and source. Research result: (1) the performance of certified teachers in SMA Negeri 1 Waingapu, on Planning and Preparation domain, teachers are in proficient category, (2) on Classroom Environment domain, teachers are in basic category, (3) on Instruction domain, teachers are in proficient category, 4) on the domain of Professional Responsibility, teachers are in basic category.